Effects of reinforcement and guidance procedures on instruction-following behavior of severely retarded children - Whitman, Thomas L. (1971)
Positive reinforcement, physical guidance, and fading procedures were used to teach two severely retarded children motor responses to a variety of verbal instructions. Subjects' responses to one set of instructions provided the focus for the training procedures. Their responses to a second set of instructions were used to assess the generalized effects of training. The frequency of responses to both sets of instructions was evaluated during Baseline 1, Training 1, Baseline 2, and Training 2 periods. During the training periods, this evaluation was made after the daily training sessions when no training procedures were in effect. Results indicated that the subjects showed pronounced increases in instruction-following behaviors (both trained and untrained) during training periods with decreases in such behavior occurring during the Baseline 2 period. The general findings demonstrate the applicability of the training procedures for producing and maintaining instruction-following behaviors in severely retarded children and for facilitating appropriate responding to instructions not directly involved in training.